2021
DOI: 10.3390/cancers13020335
|View full text |Cite
|
Sign up to set email alerts
|

Targeting E-selectin to Tackle Cancer Using Uproleselan

Abstract: E-selectin is a vascular adhesion molecule expressed mainly on endothelium, and its primary role is to facilitate leukocyte cell trafficking by recognizing ligand surface proteins. E-selectin gained a new role since it was demonstrated to be involved in cancer cell trafficking, stem-like properties and therapy resistance. Therefore, being expressed in the tumor microenvironment, E-selectin can potentially be used to eradicate cancer. Uproleselan (also known as GMI-1271), a specific E-selectin antagonist, has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 81 publications
0
34
1
Order By: Relevance
“…Selectins (cluster of differentiation 62 or CD62) are a family of cell adhesion molecules (or CAMs), that played an important role in inflammation and progression of cancer. 39,40 Moreover, Yusuf et al 41 and Katz et al 42 have reported elevated concentrations of selectins, following DMBA administration. On the other hand, interleukin-2 (IL-2) is a cytokine signalling molecule, with pleiotropic effects on the immune system, helping the body fight off infections.…”
Section: Effects On Serum Concentrations Of Interleukin-2 and Selectinmentioning
confidence: 99%
“…Selectins (cluster of differentiation 62 or CD62) are a family of cell adhesion molecules (or CAMs), that played an important role in inflammation and progression of cancer. 39,40 Moreover, Yusuf et al 41 and Katz et al 42 have reported elevated concentrations of selectins, following DMBA administration. On the other hand, interleukin-2 (IL-2) is a cytokine signalling molecule, with pleiotropic effects on the immune system, helping the body fight off infections.…”
Section: Effects On Serum Concentrations Of Interleukin-2 and Selectinmentioning
confidence: 99%
“…As selectins are physiologically important for the interactions involving leukocytes, platelets, or endothelial cells [ 109 ], it is not surprising that they play an essential role in tumor-promoting inflammation and cancer metastasis [ 131 ]. In particular, E-selectin was reportedly discovered to be upregulated during metastasis [ 132 ], representing an essential receptor in leukemia [ 133 ], and myeloma but also in solid tumors including pancreatic, prostate, colon, and breast carcinoma (reviewed in [ 134 ]). Moreover, there is strong evidence that the expression of sLe x and sLe a is also increased in many cancer types, for example, in gastrointestinal cancer, carcinoma or melanoma cells correlating with enhanced metastasis and poor prognosis [ 112 , 135 , 136 , 137 ].…”
Section: Selectinsmentioning
confidence: 99%
“…The interaction between sLe x and E-selectin is well recognized to enhance the adhesion of cancer cells to the endothelium [ 138 ], one example being leukemic cells adhering to the bone marrow [ 139 , 140 ]. Additionally, E-selectin overexpression and the subsequent interaction with the tumor-microenvironment was shown to activate pro-survival and antiapoptotic signaling via the ERK/AKT, PI3K, NF-κB, or Wnt pathway (reviewed in [ 134 ]), which promoted tumor progression, chemoresistance [ 134 ], and also the maintenance of cancer cell stemness [ 141 ]. In particular, its role in acute myeloid leukemia (AML) is well researched.…”
Section: Selectinsmentioning
confidence: 99%
See 2 more Smart Citations